2002
DOI: 10.1176/appi.ajp.159.8.1329
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Intrasynaptic Dopamine Release in Tourette’s Syndrome Measured by PET

Abstract: Greater putamen dopamine release was seen in adults with Tourette's syndrome than in comparison subjects after a pharmacologic challenge with amphetamine. These results suggest that the underlying pathobiology in Tourette's syndrome is a phasic dysfunction of dopamine transmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
137
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 243 publications
(146 citation statements)
references
References 49 publications
8
137
0
1
Order By: Relevance
“…Single-photon emission computed tomography investigations in TS have found higher DAT binding in the right caudate [635], the striatum [636-639], the putamen after amphetamine challenge [640], and the basal ganglia [641]. However, a handful of studies have found no differences in striatal DAT binding in TS [639,642-644].…”
Section: Reviewmentioning
confidence: 99%
“…Single-photon emission computed tomography investigations in TS have found higher DAT binding in the right caudate [635], the striatum [636-639], the putamen after amphetamine challenge [640], and the basal ganglia [641]. However, a handful of studies have found no differences in striatal DAT binding in TS [639,642-644].…”
Section: Reviewmentioning
confidence: 99%
“…Several brain imaging studies have investigated D-amphetamine (D-AMPH)-induced dopamine (DA) release in the striatum (Laruelle et al, 1995;Kegeles et al, 1999;Drevets et al, 2001;Singer et al, 2002;Piccini et al, 2003;Martinez et al, 2003;Volkow et al, 1994Volkow et al, , 2004. However, dopaminergic neurotransmission in cortex, thalamus, and limbic regions is believed to be significantly involved in psychosis, cognitive function, and psychostimulant drug abuse (Weinberger et al, 2001;Stevens, 1991;Kerwin and Murray, 1992;Goldman-Rakic, 1998;Yasuno et al, 2004;Koob and Le Moal, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Drugs that reduce dopamine activity, such as chlorapromazine and holoperidol (30), also reduce movements. In contrast, increased dopamine activity occurs in Tourette's syndrome (31), marked by fast, hyperkinetic movements, and early stages of Huntington's disease (32), characterized by choreiform movements.…”
Section: Discussionmentioning
confidence: 91%